2015
DOI: 10.14520/adyusbd.23061
|View full text |Cite
|
Sign up to set email alerts
|

Türki̇ye’de Harmanlanmiş Öğrenme Eği̇li̇mleri̇: Bi̇r Li̇teratür Çalişmasi

Abstract: Ertuğrul USTA  Öz Bu araştırmanın amacı, harmanlanmış öğrenme ile ilgili YÖK Ulusal Tez

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…The studies on blended learning mostly focus on the environment-method discussion. In most of these studies, blended learning and traditional learning were compared (Al-Qahtani & Higgins, 2013;Chang et al, 2014;Drysdale et al, 2013;Hamza, 2015;Smith & Suzuki, 2015), and it was found that students in blended learning environments had higher levels of achievement, motivation and attitudes when compared to those in traditional learning environments (Caputo, 2010;Drysdale et al, 2013;Hebebci & Ertugrul, 2015;Tuysuz & Balaman, 2011). Besides these studies, Cheng and Chau (2016) reported significant relationships between learning styles of learners and their online participation, between online participation and academic achievement and between achievement and satisfaction.…”
Section: Blended Learningmentioning
confidence: 99%
“…The studies on blended learning mostly focus on the environment-method discussion. In most of these studies, blended learning and traditional learning were compared (Al-Qahtani & Higgins, 2013;Chang et al, 2014;Drysdale et al, 2013;Hamza, 2015;Smith & Suzuki, 2015), and it was found that students in blended learning environments had higher levels of achievement, motivation and attitudes when compared to those in traditional learning environments (Caputo, 2010;Drysdale et al, 2013;Hebebci & Ertugrul, 2015;Tuysuz & Balaman, 2011). Besides these studies, Cheng and Chau (2016) reported significant relationships between learning styles of learners and their online participation, between online participation and academic achievement and between achievement and satisfaction.…”
Section: Blended Learningmentioning
confidence: 99%
“…Although blended learning has uncertainties in terms of costs and outcomes (Horn & Staker, 2011), research shows that blended learning contributes positively to learning performance (Graham et al, 2005;Hebebci & Usta, 2015). In the lessons in which the blended learning method is used, the continuous availability of content and materials, allocating more time to activities, the use of social networks, interaction, and participation rates are the factors that increase learner achievement (Bozkurt, 2018;Francis & Shannon, 2013;Means et al, 2009).…”
Section: Table 2 the Benefits And Challenges Of The Blended Learningmentioning
confidence: 99%
“…İlgili alan yazın incelendiğinde, harmanlanmış öğrenme modeli ile ilgili 2005-2014 yılları arasında yapılan tez araştırmaları hakkında bir makale (Hebebci & Usta, 2015) ve 2003-2014 yılları arasında yapılan tez araştırmaları (Dikmen, Ocak & Efe, 2018) ile ilgili bir tam metin bildiri olmak üzere sadece iki çalışmaya ulaşılmıştır. Bu araştırmalarda harmanlanmış öğrenme modeli konusunda gerçekleştirilen tez araştırmaları incelenirken makale ve bildiriler ile ilgili doküman incelemesi yapılmamıştır.…”
Section: şEkil 1 Harmanlanmış öğRenme Modeliunclassified